Recurrent angioedema, Guillain-Barré, and myelitis in a girl with systemic lupus erythematosus and CD59 deficiency syndrome - Javadi Parvaneh, Vadood (Auto Immun Highlights, 2020)
BACKGROUND: CD59 deficiency is a congenital mutation disorder in complement pathway which can present with various manifestations. CASE PRESENTATION: Herein, we presented an adolescent 16-years-old girl with recurrent attacks of Guillain-Barre in early childhood and then recurrent attacks of angioedema, paresthesia, and myelitis. Finally, she presented with quadriplegia, malar rash, proteinuria, lymphopenia, and high titer of antinuclear antibody. So, the patient developed systemic lupus erythematosus. Furthermore, we performed whole exome sequencing which revealed homozygote mutations in CD59 for the patient and heterozygote one for her parents. CD flow cytometry showed less than 1 percent expression of CD59 on the surface of the patient’s peripheral blood cells confirming the disorder. So, she had CD59 deficiency. The patient’s episodes were managed with plasma exchanges, corticosteroids, Cyclophosphamide, and Mycophenolate Mofetil which induced and maintained remission. CONCLUSION: CD59 deficiency can be presented with various clinical features such as neurologic, hematologic, dermatologic, and rheumatologic problems including systemic lupus erythematosus.